A Stochastic Phylogenetic Algorithm for Mitochondrial DNA Analysis - Corona-Ruiz, M.; Hernandez-Cabrera, Francisco; Cantú-González, José Roberto; González-Amezcua, O.; Javier Almaguer, Francisco (Frontiers in Genetics, 2019)
This paper presents an exploratory analysis of the mitochondrial DNA (mtDNA) of 32 species in the subphylum Vertebrata, divided in 7 taxonomic classes. Multiple stochastic parameters, such as the Hurst and detrended fluctuation analysis (DFA) exponents, Shannon entropy, and Chargaff ratio are computed for each DNA sequence. The biological interpretation of these parameters leads to defining a triplet of novel indices. These new functions incorporate the long-range correlations, the probability of occurrence of nucleic bases, and the ratio of pyrimidines-to-purines. Results suggest that relevant regions in mtDNA can be located using the proposed indices. Furthermore, early results from clustering algorithms indicate that the indices introduced might be useful in phylogenetic studies.